Development of LSLC-Based Collaborative Learning Model Learning Tools And Their Effects on Critical Thinking Skills - Evi Takrimatul Ailiyyah; Pambudi, Didik Sugeng; Fatekurohman, Mohamad; Kurniati, Dian; Susanto (Universitas Islam Lamongan, 2024)
The purpose of this study is to develop collaborative learning-based learning resources and their impact on students' capacity for critical thought. This study used a combination of methods, namely development research (R&D) with Thiagarajan 4D model and experimental research. Data was collected through observations, questionnaires, tests, and interviews. The validity coefficients for the Teaching Module, worksheet, and test were 3.80, 3.80, and 3.70, respectively. Observations showed that 96% of the learning tools met practical criteria. The tools were effective, with 93% of student activities rated very good, 96% of students giving positive responses, and 85% achieving learning completion. A t-test (sig = 0.007) confirmed the collaborative learning tool based on LSLC significantly enhanced students' critical thinking skills.